Assessment of executive function declines in presymptomatic and mildly symptomatic familial frontotemporal dementia: NIH‐EXAMINER as a potential clinical trial endpoint. Issue 1 (8th January 2020) - Staffaroni, Adam M.; Bajorek, Lynn; Casaletto, Kaitlin B.; Cobigo, Yann; Goh, Sheng‐Yang M.; Wolf, Amy; Heuer, Hilary W.; Elahi, Fanny M.; Ljubenkov, Peter A.; Dever, Reilly; Kornak, John; Appleby, Brian; et al.
Abstract: Introduction: Identifying clinical measures that track disease in the earliest stages of frontotemporal lobar degeneration (FTLD) is important for clinical trials. Familial FTLD provides a unique paradigm to study early FTLD. Executive dysfunction is a clinically relevant hallmark of FTLD and may be a marker of disease progression. Methods: Ninety‐three mutation carriers with no symptoms or minimal/questionable symptoms ( MAPT, n = 31; GRN, n = 28; C9orf72, n = 34; Clinical Dementia Rating scale plus NACC FTLD Module < 1) and 78 noncarriers enrolled through Advancing Research and Treatment in Frontotemporal Lobar Degeneration/Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects studies completed the Executive Abilities: Measures and Instruments for Neurobehavioral Evaluation and Research (NIH‐EXAMINER) and the UDS neuropsychological battery. Linear mixed‐effects models were used to identify group differences in cognition at baseline and longitudinally. We examined associations between cognition, clinical functioning, and magnetic resonance imaging volumes. Results: NIH‐EXAMINER scores detected baseline and differences in slopes between carriers and noncarriers, even in carriers with a baseline Clinical Dementia Rating scale plus NACC FTLD Module = 0. NIH‐EXAMINER declines were associated with worsening clinical symptoms and brain volume loss. Discussion: The NIH‐EXAMINER is sensitive to cognitive changes in presymptomatic familial FTLD and is a promising surrogate endpoint.